2018
DOI: 10.11604/pamj.2018.29.174.13098
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and outcome of ill critical patients with influenza A infection

Abstract: IntroductionTo describe all patients admitted to Tunisian intensive care unit with a diagnosis of influenza A/H1N1 virus infection after the 2009 influenza pandemic and to analyse their characteristics, predictors of complications and outcome.MethodsAll patients with influenza > 18-years-old hospitalized to the ICU department of Tunisian University hospital of Sousse, between December 1, 2009 and March 31, 2016, with a positive influenza A/H1N1/09 reverse transcriptase polymerase chain reaction (RT-PCR) from a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 18 publications
0
14
0
1
Order By: Relevance
“…There were a few clinical reports about a varies of respiratory infection patients. However, in these studies, the proportion of patients with respiratory symptoms undergoing chest CT examinations did not exceed 20% and, furthermore, the patients were not randomized into groups ( 12 , 16 , 23 25 ). Whereas the limitations of previously research, this study conducted a comprehensive collection of chest CT data for patients with influenza-like symptoms and compared the difference of normal and abnormal chest CT cases.…”
Section: Discussionmentioning
confidence: 99%
“…There were a few clinical reports about a varies of respiratory infection patients. However, in these studies, the proportion of patients with respiratory symptoms undergoing chest CT examinations did not exceed 20% and, furthermore, the patients were not randomized into groups ( 12 , 16 , 23 25 ). Whereas the limitations of previously research, this study conducted a comprehensive collection of chest CT data for patients with influenza-like symptoms and compared the difference of normal and abnormal chest CT cases.…”
Section: Discussionmentioning
confidence: 99%
“…Cabe destacar que, tal y como refieren otros estudios no existen prácticamente diferencias en la afectación por géneros (9) . En relación con los antecedentes patológicos de interés, nuestro estudio muestra que aproximadamente un 90% de los pacientes padecía algún antecedente, dato por encima de los estudios previos, que muestran un porcentaje alrededor del 70% (10) . Los antecedentes de etiología cardíaca resultan mayores en incidencia en nuestro estudio, seguido de la patología respiratoria y renal.…”
Section: Discussionunclassified
“…Although data on risk factors for influenza are key to guide targeted influenza vaccination, few studies have addressed topics on the risk factors for influenza [95][96][97][98][99] . Results from these studies reported that underlying medical conditions such as HIV, tuberculosis, diabetes, chronic respiratory diseases, pregnancy and patient's age contribute strongly to influenza associated hospitalization or death.…”
Section: Influenza Risk Factors and Co-morbiditiesmentioning
confidence: 99%
“…Moreover, Barakat et al in Morocco found that influenza cases associated with hypertension (aOR, 28.2), neurological disorders (aOR), obesity (aOR, 7.1), as well as pregnancy (aOR, 2.5) were at increased risk of death 96 . Furthermore, Bouneb et al in Tunisia using logical regression reported that acute respiratory distress syndrome (ARDS) (OR = 27; 95%CI: 3.62-203.78) was the only factor significantly associated with severe outcomes of influenza cases 99 . Influenza associated co-morbidities have been studied nine articles from 3 countries 101-105, 107-109, 134, 215 .…”
Section: Influenza Risk Factors and Co-morbiditiesmentioning
confidence: 99%